Iron as the Key Modulator of Hepcidin Expression in Erythroid Antibody-Mediated Hypoplasia. (17th December 2014) - Fernandes, J. C.; Garrido, P.; Ribeiro, S.; Rocha-Pereira, P.; Bronze-da-Rocha, E.; Belo, L.; Costa, E.; Reis, F.; Santos-Silva, A.
Abstract : Erythroid hypoplasia (EH) is a rare complication associated with recombinant human erythropoietin (rHuEPO) therapies, due to development of anti-rHuEPO antibodies; however, the underlying mechanisms remain poorly clarified. Our aim was to manage a rat model of antibody-mediated EH induced by rHuEPO and study the impact on iron metabolism and erythropoiesis. Wistar rats treated during 9 weeks with a high rHuEPO dose (200 IU) developed EH, as shown by anemia, reduced erythroblasts, reticulocytopenia, and plasmatic anti-rHuEPO antibodies. Serum iron was increased and associated with mRNA overexpression of hepatic hepcidin and other iron regulatory mediators and downregulation of matriptase-2; overexpression of divalent metal transporter 1 and ferroportin was observed in duodenum and liver. Decreased EPO expression was observed in kidney and liver, while EPO receptor was overexpressed in liver. Endogenous EPO levels were normal, suggesting that anti-rHuEPO antibodies blunted EPO function. Our results suggest that anti-rHuEPO antibodies inhibit erythropoiesis causing anemia. This leads to a serum iron increase, which seems to stimulate hepcidin expression despite no evidence of inflammation, thus suggesting iron as the key modulator of hepcidin synthesis. These findings might contribute to improving new therapeutic strategies against rHuEPO resistance and/or development of antibody-mediated EH in patients under rHuEPO therapy.